Peromyscus spp. Deer Mice as Rodent Model of Acute Leptospirosis - Ellie J. Putz; Claire B. Andreasen; Paola Boggiatto; Mitchell V. Palmer; Luis G.V. Fernandes; Bienvenido W. Tibbs-Cortes; Judith A. Stasko; Camila Hamond; Steven C. Olsen; Jarlath E. Nally (Emerging Infectious Diseases, 2025)
Leptospirosis is a global zoonotic disease affecting humans, wildlife, companion, and domestic animals. Incidental hosts can contract the disease directly or indirectly from asymptomatic reservoir hosts, most commonly small rodents. The Golden Syrian hamster is recognized as the dominant rodent model for acute leptospirosis because the animals are susceptible to many serovars and are used to maintain laboratory strains and test bacterin vaccine efficacy. However, hamsters are primarily used in survival-based studies, and investigations into host immune response and disease pathogenesis are limited. We found that Peromyscus leucopus white-footed deer mice are susceptible to acute leptospirosis, and thus might be an alternative rodent model. Furthermore, similar to hamsters, deer mice produce circulating foamy macrophages in response to Leptospira challenge. Deer mice exhibit differences in response to different serovars, clinical disease severity, kidney and liver lesions, and an overall sex effect, with male mice demonstrating more severe clinical signs and higher bacterial burden.